Improving Communication in Agbiotech Projects: Moving Toward a Trust-centered Paradigm - Obidimma Ezezika; Justin Mabeya (Journal of Applied Communications, 2014)
Communication with end users about agricultural biotechnology does not necessarily lead to commensurate adoption of biotech crops. Agbiotech communication implies challenges like disagreement between proponents and opponents of genetically modified (GM) technology and media influence on public opinion, both of which can negatively impact public trust in, and thus adoption of, biotech crops. We argue that communication strategies for introducing biotech crops should focus on building and fostering trust between project partners developing biotech crops and the community they intend to serve to facilitate effective adoption of the crops. Strategies should include a combination of knowledge dissemination; early and continuous communication; provision of training; emphasis on end-user benefits; and transparency about agbiotech projects – all with the aim of building and fostering trust between partners of agbiotech projects and the community.
Keywords: agricultural biotechnology; biotech crops; communication; trust